Dietary supplement of Acanthopanax senticosus decoction formula improves immune response via intestine flora of rabbits - Nie, Jing; Liu, Qin; Huang, Shihui; Wang, Jiafu; Niu, Xi; Ran, Xueqin (Frontiers in Microbiology, 2025)
Young rabbits are sensitive to surrounding changes and conditioned pathogens in intestine which might result in slow inflammation and diarrhea after microbial invasion. Traditional medicine herbs could provide efficacious treatment on slow infection and inflammation. The present research designed an Acanthopanax senticosus (ACS) formula consisted of five types of Chinese herbs including Acanthopanax senticosus (Rupr & Maxim) Harms (Ciwujia in Chinese), Astragalus membranceus (Fisch) Bge (Huangqi in Chinese), Indigo naturalis (Qingdai in Chinese), Houttuynia cordata Thunb (Yuxingcao in Chinese), and Glycyrrhizae radix et Rhizoma (Gancao in Chinese). The effects of ACS decoction supplement were investigated via determination of cytokines and growth performances of young rabbits, and the flora in intestinal digesta from six fragments were further explored using 16S rRNA gene sequencing technology. Compared to the control group, rabbits supplied with different doses of ACS decoction possessed lower diarrhea and death rates, together with the IL-10 concentration, while the declined IL-1β and IL-12 levels and inflammatory factor gene expressions in intestinal tissues. Additionally, ACS addition changed the diversity of flora in each segments of intestine. Functional prediction on abundances of genera enriched to seven KEGG immunity pathways. Moreover, strong correlations were determined between the abundance of bacteria with interleukins contents, and the predictive immune signaling abundances, respectively. Especially, ACS exhibited anti-inflammation effects via decreasing the abundances of Bacteroides, Clostridia_vadinBB60_group, NK4A214_group, and dgA_11_gut_group in intestine of young rabbits. In conclusion, dietary supplement with ACS exerted diarrhea-reducing effects, and improved immunity homeostasis by modulating intestinal flora diversity in young rabbits.